7+5s-6=7s+7-5s

Simple and best practice solution for 7+5s-6=7s+7-5s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+5s-6=7s+7-5s equation:


Simplifying
7 + 5s + -6 = 7s + 7 + -5s

Reorder the terms:
7 + -6 + 5s = 7s + 7 + -5s

Combine like terms: 7 + -6 = 1
1 + 5s = 7s + 7 + -5s

Reorder the terms:
1 + 5s = 7 + 7s + -5s

Combine like terms: 7s + -5s = 2s
1 + 5s = 7 + 2s

Solving
1 + 5s = 7 + 2s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-2s' to each side of the equation.
1 + 5s + -2s = 7 + 2s + -2s

Combine like terms: 5s + -2s = 3s
1 + 3s = 7 + 2s + -2s

Combine like terms: 2s + -2s = 0
1 + 3s = 7 + 0
1 + 3s = 7

Add '-1' to each side of the equation.
1 + -1 + 3s = 7 + -1

Combine like terms: 1 + -1 = 0
0 + 3s = 7 + -1
3s = 7 + -1

Combine like terms: 7 + -1 = 6
3s = 6

Divide each side by '3'.
s = 2

Simplifying
s = 2

See similar equations:

| 3-12y=7y+7 | | 4/5x-48 | | (w^9)^(1/3) | | (-6)+3.98= | | 2x^3+4x^2+4x+8=0 | | 9+9m-4=7m+45-3m | | 6(r-14)+2(r-3)=14 | | 2(3y-7)=2(3+8y) | | 2[2x-1]=18 | | 6(a-14)+5(a-18)=2 | | Y^2-24y+144=-100 | | 2(4*s-16)-5*s=-5 | | 2y=58 | | 95+76=195 | | 4x=7x-1 | | y=4.25x-3 | | 8.1+3.8*h-5.6h=-7.2 | | X(7×10^4)/3=4×10^2 | | j-81=3 | | 9x-4=3x-11 | | 7(2v-1)+2=51 | | 81+21=120 | | 3y^2+11y+9=0 | | 21x=16x-7 | | 4.3*t-2.1*t-2.3=7.6 | | [x-6]=10 | | 12x+2=4x+1 | | (2x+39)=(7x+9) | | 8-3*x=17 | | 5x+3yx=10 | | [-4x]=16 | | 9x^4-25x=0 |

Equations solver categories